Computer simulation of the harmonic and reactive power compensator / Ismail Ishak - Ishak, Ismail (1992)
The overall aim of this project was to use the package known as Visula to simulate the hardware namely a Harmonic and Reactive Power Compensator. The hardware part was built by Mr. Mohd. Zaki Abdullah (Project Advisor) during his Master Degree project. By using Visula, the analysis can be done easily. Besides, the package also offered the variety of advantages in designing, constructing and analyzing the electronic circuits. This report is based on the simulation of the current control loop of the compensator.